Geographical variation in DXA bone mineral density in young European men and women. Results from the Network in Europe on male osteoporosis (NEMO) study - Kaptoge, Stephen (2008)
We collected population-based young normal hip and spine BMD data from 17 centres across Europe to assess between centre differences and to compare reference values with the US NHANES-III data. There was strong evidence of between country heterogeneity, but not between centres within countries. Hip BMD mean values were lower in European women, but SD's differed little from the NHANES-III USA results in both sexes. It may be necessary to adjust NHANES-III based T-scores by adding/subtracting a country-specific adjustment factor.Introduction